The limits to openness: Co-working, design and social innovation in the neoliberal city. (June 2020) - Lorne, Colin
This article examines the emergence of 'open' urban economic projects that promote the transformative potential of social innovation and civic enterprise. By putting the burgeoning literature on an open paradigm of work and innovation within cultural economic geography into dialogue with scholarship on open cities, I problematize the inherently progressive framing of openness. The paper makes two contributions. First, it emphasises how open narratives encourage entrepreneurial communities that manifest as individualization-masked-as-collectivism. It argues efforts to design new spaces of social innovation through the blurring of boundaries simultaneously reproduce social and material exclusions. Second, it demonstrates how the championing of open ecosystems of social innovation intersects with austerity localism. New modes of state withdrawal are facilitated through co-creation, crowdfunding and social enterprise. Illustrated through research into a co-working space in London set up in response to the 2007–2008 economic crisis, I reveal the geographies of exclusion, enclosure and exploitation embedded in the pursuit of openness. Against the claims of enabling conditions for progressive civic futures, I establish the limits to openness whereby such ideas are easily assimilated into the processes of neoliberalisation that they seek to reject.